Analysis of Alternative Financial Reporting Integration with Traditional Financial Reporting for Corporate Transparency - Dasila, Rifqa Ayu (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the integration of alternative financial reporting, including environmental, social, and governance (ESG) disclosures, with traditional financial reporting to enhance corporate transparency and foster stakeholder trust. It examines how integrated reporting bridges the gap between economic and non-financial disclosures by identifying key patterns, challenges, and best practices. Research Design and Methodology: A qualitative approach was employed using a Systematic Literature Review (SLR) method. The study reviewed scholarly articles and industry reports published since 2018 to assess trends, technical and strategic challenges, and recommendations for implementing integrated reporting across various sectors and regions. Findings and Discussion: The findings suggest that integrated reporting fosters stakeholder trust by offering a comprehensive view of corporate performance and aligning sustainability initiatives with financial outcomes. However, challenges such as inconsistent reporting standards, technological limitations, and data management constraints persist. Investments in data systems, staff training, and proactive communication improve report credibility and consistency. A flexible yet standardized framework is necessary to accommodate diverse regulatory environments. Implications: This study offers practical recommendations for companies to enhance reporting through technology upgrades and workforce development initiatives. It also highlights the need for global harmonization of ESG reporting standards for regulators and investors. Additionally, it contributes to academic discourse by expanding research on stakeholder theory and integrated reporting, supporting sustainable and transparent corporate governance.